2013
DOI: 10.2399/prn.13.0213004
|View full text |Cite
|
Sign up to set email alerts
|

The effect of maternal smoking during pregnancy on Doppler parameters

Abstract: Objective: It is suggested that smoking has adverse effects on placenta development by decreasing placental vascularization. Cigarette exposure is associated with intrauterine and perinatal death, preterm labor, ablatio placenta, placenta previa and intrauterine growth retardation. The aim of this study is to investigate the effect of smoking on fetal Doppler ultrasound waveforms and its pathophysiological relationship with fetal birth weight. Methods: The study was conducted in Gynecology and Obstetrics Depar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Relatedly, prenatal smoking has been linked to suboptimal utero-placental oxygen and blood flow and is considered as one of the major risk factors for a wide array of gestational complications, including PTB and LBW (67). Aside from being the most influential risk node, we found that prenatal smoking was directly linked to LBW.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Relatedly, prenatal smoking has been linked to suboptimal utero-placental oxygen and blood flow and is considered as one of the major risk factors for a wide array of gestational complications, including PTB and LBW (67). Aside from being the most influential risk node, we found that prenatal smoking was directly linked to LBW.…”
Section: Discussionmentioning
confidence: 65%
“…According to the 2017 Global Burden of Diseases, Injuries, and Risk Factors Study , smoking was among the top risk factors for burdens of disease and mortality among women (66). Relatedly, prenatal smoking has been linked to suboptimal utero-placental oxygen and blood flow and is considered as one of the major risk factors for a wide array of gestational complications, including PTB and LBW (67). Aside from being the most influential risk node, we found that prenatal smoking was directly linked to LBW.…”
Section: Discussionmentioning
confidence: 99%
“…Along with PTB and LBW, the 2017 Global Burden of Diseases, Injuries, and Risk Factors Study identified smoking as one of the top risk factors for burdens of disease and mortality among women (Stanaway et al, 2018 ). Relatedly, prenatal smoking has been linked to suboptimal utero-placental oxygen and blood flow and is considered as one of the major risk factors for a wide array of gestational complications, including PTB and LBW (Janbakhisov, Emekçi, Ça, & Altunyurt, 2013 ). Aside from being the most influential risk node, we found that prenatal smoking was associated with LBW.…”
Section: Discussionmentioning
confidence: 99%